Macroscopic diffusivity in concrete determined by computational homogenization. (31st May 2012) - Nilenius, Filip; Larsson, Fredrik; Lundgren, Karin; Runesson, Kenneth
SUMMARY: Effective moisture and chloride ion diffusivity coefficients for concrete are determined by computational homogenization, where concrete is modeled on the mesoscale as a heterogenous three‐phase composite material. By imposing moisture and chloride ion gradients on a representative volume element, effective macroscale properties are obtained through finite element analysis. A parametric study of the effects of the ballast content was carried out. The numerical results correspond well with an estimate of the Hashin–Shtrikman type available in the literature. The computational homogenization strategy proposed here also includes the interfacial transition zone, and its influence on the effective diffusivity coefficients is assessed. Copyright © 2012 John Wiley & Sons, Ltd.